REINVENTING MAJAPAHIT STYLE IN ACEH SULTANATE ARCHITECTURE - Fadhil, Muhammad Naufal; Putri, Aji Sofiana (Border: Jurnal Arsitektur, 2025)
This article analyses the impact of the Majapahit architectural style on the Sultanate of Aceh, drawing inspiration from the 'Majapahit Style' as defined within Balinese architecture. Studies of Aceh Sultanate Architecture reveal features resembling the Majapahit Style, suggesting a cultural and historical connection. This study examines the historical context and compares architectural and urban typologies in Majapahit and Aceh through a literature review and analysis of artefacts. It identifies two key typologies demonstrating Majapahit influence: Religious Structures and Royal Urban Landscapes. This analysis critiques the conventional narratives that categorise architectural history into discrete religious periods (Hindu, Buddhist, or Islamic), highlighting the interconnections and varied histories in architecture and urban planning. The findings highlight the significance of acknowledging the cross-cultural influences that have shaped Aceh's built environment, challenging simplistic classifications based on religion or culture. This research illustrates the persistent impact of Majapahit architectural traditions on the Sultanate of Aceh particularly in the adoption of Meru-style mosques and urban planning approaches. The study emphasises the relationship between culture and religion influencing architectural expression, promoting a more profound comprehension of Aceh's built environment.